Insight into the Functional and Structural Properties of 3‐Arylcoumarin as an Interesting Scaffold in Monoamine Oxidase B Inhibition. Issue 7 (8th April 2014) - Matos, Maria João; Vilar, Santiago; García‐Morales, Verónica; Tatonetti, Nicholas P.; Uriarte, Eugenio; Santana, Lourdes; Viña, Dolores
Abstract The design, synthesis, pharmacological evaluation, and theoretical studies of a new series of halogenated 3‐arylcoumarins were carried out with the aim of finding new structural and biological features. This series displays several alkyl, hydroxy, halogen, and/or alkoxy groups in both benzene rings of the 3‐arylcoumarin scaffold. Most of the compounds studied show high affinity and selectivity for the human monoamine oxidase B (hMAO‐B) isoenzyme, with IC50 values in the low nanomolar and picomolar range. Most of the evaluated compounds display higher MAO‐B inhibitory activity and selectivity than selegiline (the reference compound). Coumarin 12 (3‐(3‐bromophenyl)‐6‐methylcoumarin) is the most active compound (IC50=134 pM), being 140‐fold more active than selegiline and showing the highest specificity for hMAO‐B. To better understand the structure–activity relationships, docking experiments were carried out on human monoamine oxidase (A and B) structures. Finally, the prediction of passive blood–brain partitioning, based on in silico derived physicochemical descriptors, was performed.